Hematological Indicators Assessing Severity in Dengue Patients - Ansa Kulsoom Rehman, Humaira Taj Niazi, Laila Bahadur, Saba Khan, Mehreen Farooq, Asfandyar Shah Roghani (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Dengue is viral disease of human transmitted by Aedes aegypti mosquito. The clinical signs and symptoms of dengue infection range significantly, from mild dengue fever to a severe illness. Objective: Our study aims to describe the potential predictive hematological parameters which are associated with severity in dengue patients. Methodology: This study was descriptive study conducted at the department of Pathology (Hematology), Maqsood Medical Complex and General Hospital, Peshawar, for duration of six months from 1st May 2022 to 31st October 2022. Blood samples were taken aseptically from all the included patients and were sent to the hospital diagnostic laboratory where the hematological parameters were determined. All the data was collected in a pre-designed proforma. The data analysis was done by using IBM SPSS version 23. Results: In the current study, a total of 160 patients were enrolled. There were 102 (63.75%) male patients while female patients were 56 (36.25%). Based on the hematological parameters, the mean (±SD) Hematocrit (%), Hemoglobin (g/dl), White cell count (/µL), Lymphocytes(/µL), Neutrophils (%) and Platelets (/µL) in non severe dengue cases vs severe dengue cases were 39.2 (±5.1)% vs 42.3 (±4.3)%, 12.5 (±0.9) g/dl vs 13.9 (±1.8) g/dl, 3290 (±1.4) /µL vs 4750 (±1.6) /µL, 40.6 (±12.19)/µL vs 46.1 (±9.96) /µL, 44.4 (±16.56)% vs 49.4 (±12.44) % and 10,5000 (±1.12) /µL vs 56,000 (±2.36)/µL respectively. Conclusion: Our study concludes that some common hematological markers have a substantial correlation with the severity of dengue illness. Keywords: Hematological indicators; severe dengue; Non-severe dengue